2017
DOI: 10.1097/md.0000000000007566
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CG single nucleotide polymorphisms are associated with poor responsiveness to clopidogrel and increased risk of ischemia in patients with coronary heart disease

Abstract: A positive correlation may exist between PIK3CG SNPs (rs1129293 and rs17398575) and patients with poor responsiveness to clopidogrel. These findings show that this factor may contribute to an increased risk of ischemia in patients suffering from CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…PIK3CG protein belonged to the member protein of pI3/pI4-kinase and was an extracellular signaling critical modulator; including the cell-cell adhesion mediated by E-cadherin that importantly act proper maintenance with its integrity of structural epithelia [32] . In a combined meta-analysis of carotid plaques confirmed the rs17398575 SNP in PIK3CG gene that might induce an 18% chances plaque formation, showed PIK3CG had important clinical significance for higher chances of aggregation in platelet leading to acute coronary syndromes [33] . In our study, the results showed that PIK3CG were up-regulated in stable atherosclerotic plaques samples, compared with ruptured atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 97%
“…PIK3CG protein belonged to the member protein of pI3/pI4-kinase and was an extracellular signaling critical modulator; including the cell-cell adhesion mediated by E-cadherin that importantly act proper maintenance with its integrity of structural epithelia [32] . In a combined meta-analysis of carotid plaques confirmed the rs17398575 SNP in PIK3CG gene that might induce an 18% chances plaque formation, showed PIK3CG had important clinical significance for higher chances of aggregation in platelet leading to acute coronary syndromes [33] . In our study, the results showed that PIK3CG were up-regulated in stable atherosclerotic plaques samples, compared with ruptured atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 97%
“…Rebrova et al ( 5 ) demonstrated that there was no association between the risk of clopidogrel resistance and the presence of polymorphic variants of platelet receptor genes P2RY12 and GpIII. However, Li et al ( 6 ) reported that a positive correlation might exist between PIK3CG SNPs (rs1129293 and rs17398575) and patients unresponsive to clopidogrel. In the present article, authors concluded that the presence of the CYP2C19*2 or *3 mutant allele was significantly associated with attenuated platelet response to clopidogrel and increased risk of clopidogrel resistance, although there was no obvious connection between presence of ABCB1 mutant allele and risk of clopidogrel resistance.…”
mentioning
confidence: 99%